2018
DOI: 10.1097/rlu.0000000000002237
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Costochondritis Caused by Aspergillus Diagnosed by 18F-FDG PET/CT

Abstract: Thoracic pain is an entity that can be difficult to diagnose etiologically. Once the cardiac origin has been ruled out, the rheumatologic, neoplastic, and infectious causes have to be taken into account. We present the case of a patient with atypical chest pain after triple-bypass surgery in whom F-FDG PET/CT scan showed an important uptake of the radiopharmaceutical in costal cartilages, in relation to pan-costochondritis due to Aspergillus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Case reports have shown that patients who clinically presented with LC were eventually con rmed to have fungal infections such as Cryptococcal infection, invasive Aspergillus infection, or tuberculosis and granulomatous lesions [8][9][10][11][12][13][14] . Aside from malignant tumors, other benign lesions or certain infections can show increased glucose metabolism and present with similar manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports have shown that patients who clinically presented with LC were eventually con rmed to have fungal infections such as Cryptococcal infection, invasive Aspergillus infection, or tuberculosis and granulomatous lesions [8][9][10][11][12][13][14] . Aside from malignant tumors, other benign lesions or certain infections can show increased glucose metabolism and present with similar manifestations.…”
Section: Discussionmentioning
confidence: 99%